2020
DOI: 10.1186/s40462-020-00218-6
|View full text |Cite
|
Sign up to set email alerts
|

Riders on the storm: loggerhead sea turtles detect and respond to a major hurricane in the Northwest Atlantic Ocean

Abstract: Background Extreme weather events, including hurricanes, have considerable biological, ecological, and anthropogenic impacts. Hurricane Irene caused substantial economic damage when it hit the Mid-Atlantic Bight (MAB) off of the eastern United States in August of 2011. The MAB is highly stratified during the summer when a strong thermocline separates warm, surface water from deep, cold water, and this oceanographic phenomenon makes modeling hurricane strength difficult. Loggerhead sea turtles ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Despite the recordbreaking winds and extreme storm surge, tags on five of the six turtles tracked during landfall continued transmissions post-storm thereby confirming turtle survival. There are multiple strategies that turtles utilize to survive during and after extreme weather events including altering dive behavior, increasing home range size and shifting habitat use [29][30][31] . These studies have typically involved larger samples sizes 30 or have documented long-distance movements 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the recordbreaking winds and extreme storm surge, tags on five of the six turtles tracked during landfall continued transmissions post-storm thereby confirming turtle survival. There are multiple strategies that turtles utilize to survive during and after extreme weather events including altering dive behavior, increasing home range size and shifting habitat use [29][30][31] . These studies have typically involved larger samples sizes 30 or have documented long-distance movements 31 .…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple strategies that turtles utilize to survive during and after extreme weather events including altering dive behavior, increasing home range size and shifting habitat use [29][30][31] . These studies have typically involved larger samples sizes 30 or have documented long-distance movements 31 . The turtles tracked in SJB during Hurricane Michael showed no large-scale movements or changes in behavior in response to the storm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acoustic telemetry has shown that some juvenile marine turtles actively select for manmade structures over natural habitats, which could prompt small-scale shifts in habitat use as the number of jetties and other shoreline stabilization structures increase with rising sea levels (Renaud et al, 1995;MacDonald et al, 2013;Crear et al, 2017;Matley et al, 2019;Oppenheimer et al, 2019). As storm frequency and intensity increase, knowledge of marine turtles' response and survivability to storms is important (Fuentes and Abbs, 2010;Fuentes et al, 2019;Crowe et al, 2020). Matley et al (2020) and Lamont et al (2021) assessed this response when separate Category 5 hurricanes moved over their passive array study sites.…”
Section: Threats Impacts and Conservationmentioning
confidence: 99%
“…We recently employed eDNA‐based approaches to study the shedding of the virus (ChHV5) associated with this disease, and these results, combined with the results of this study, can provide insight into the health and population status of wild sea turtles inhabiting our study sites (Farrell, Yetsko, et al, 2021; Yetsko et al, 2020). With increasing habitat degradation and vulnerability to threats, already threatened sea turtle populations are at increasing risk, therefore pathogen and population monitoring is crucial to aiding their survival (Crowe et al, 2020; Eastman et al, 2020; Gomez‐Ramirez et al, 2020; Marn et al, 2017). In this study we developed and validated qPCR assays in a sea turtle rehabilitation setting and we conducted field trials to detect, quantify and assess sea turtle species ( C .…”
Section: Introductionmentioning
confidence: 99%